EFL Teachers’ Perception and Challenges in Implementing Collaborative Writing - Nurul Hakimah Hafid; Isti Siti Saleha Gandana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Writing skill, compared to the other three language skills, namely listening, reading and speaking, tends to be more difficult and time-consuming to teach, and has not enough attention to teach and practice. Collaborative writing therefore can become one of the ways to help students develop their writing skills which reinforce them to produce a proper text. Hence, this study aims to investigate teachers’ perceptions and challenges in implementing collaborative writing in the EFL classroom. The study employed a phenomenology research design with five senior high school teachers who have experienced in applying collaborative writing in their teaching process. This study was conducted by using the interview section as a single data collection technique. In terms of teachers’ perception in utilizing collaborative writing, the findings revealed that teachers mentioned some positive perceptions toward the implementation of collaborative writing seen from four aspects; social, psychological, academic, and assessment. Meanwhile, in terms of challenges, it is classified into three segments; learners, instruction, and classroom management.